PENGARUH E-COMMERCE TERHADAP MINAT BELI KONSUMEN PADA AYU BUTIK KOTA PAGAR ALAM - Laili Dimyati; Yesita Astarina; Aldini Nofta Martini (LPPM ITBis Lembah Dempo, 2022)
This study aimed to determine the effect of e-commerce’s application on the consumer buying interest in “Ayu Butik” Pagar Alam. Type of research is explanatory research or research explanation using hypothesis testing and a quantitative approach. The population is 157 consumers of Ayu Butik Pagar Alam who shop during May 2020. Data used is result of answers from consumer questionnaires which distributed to the research sample of 69 people obtained through the calculation of the Slovin formula. The analyze technic used is descriptive statistics and multiple linear regression analysis. These result showed that variables e-commerce has a positive significance effect on consumer buying interest in Ayu Butik Pagar Alam. The effect of e-commerce on consumer buying interest is only 28,7%, while the remaining 71,3% influenced by other variables besides e-commerce which are not researched in this study.